1997
DOI: 10.1046/j.1464-410x.1997.28314.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of cigarette‐smoke exposure on plasma testosterone, luteinizing hormone and follicle‐stimulating hormone levels in male rats

Abstract: Objectives To determine the effects of long-term cigarette were no significant changes in testosterone in the control rats. The mean plasma LH and FSH levels of smoking on the levels of plasma testosterone, luteinizing hormone (LH) and follicle-stimulating hormone the two groups did not change significantly after exposure. In rats exposed to smoke, histological exam-(FSH) in male adult rats and to examine morphological and histological changes in the testes.ination of the testes showed fewer Leydig cells and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
4
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 3 publications
(5 reference statements)
2
30
4
1
Order By: Relevance
“…Peltola et al (1996) have shown that ROS can damage critical components of the steroidogenetic pathway in Leydig cells, including steroidogenic acute regulatory (StAR) protein (Diemer et al, 2003). The reduction in the synthesis and release of testosterone could be exacerbated by a reduction in the population of Leydig cells via apoptosis as exemplified in data on Leydig cells from rats exposed to cigarette smoke (Yardimci et al, 1997). Our data show a decrease in the interstitial volume and weight in BaP-exposed versus UNC rat testis histological preparations, suggesting the loss of Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…Peltola et al (1996) have shown that ROS can damage critical components of the steroidogenetic pathway in Leydig cells, including steroidogenic acute regulatory (StAR) protein (Diemer et al, 2003). The reduction in the synthesis and release of testosterone could be exacerbated by a reduction in the population of Leydig cells via apoptosis as exemplified in data on Leydig cells from rats exposed to cigarette smoke (Yardimci et al, 1997). Our data show a decrease in the interstitial volume and weight in BaP-exposed versus UNC rat testis histological preparations, suggesting the loss of Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…19 In a study, Yardımcı et al reported that exposure to cigarette smoke decreases the testosterone level and Leydig cell number in rats. 13 In another study by Yamamoto and associates, secretory dysfunction of the Leydig cells, deficiency in sperm maturation and spermatogenesis, decreased testosterone response to hCG stimulation were shown after exposure of rats to cigarette smoke. 20 Despite all this intensive work, the study number about negative effects of ETS on testicular functions is quite rare in children.…”
Section: Discussionmentioning
confidence: 96%
“…Significantly increased, 12 decreased and unchanged levels of total testosterone in male smokers have been reported in various studies. 12,13,17 In a study semen parameters and hormone concentrations of infertile smokers had been compared with infertile non-and ex-smokers. In this study Trummer et al reported that smoking does not affect conventional semen parameters, but increases serum free and total testosterone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations